Pola Pendidikan Nabi SAW dalam Hadits - Lestari, Umi Fitri; Fitriyadi, M.; Sahbana, M. Dwi Rahman (Asian Journal of Islamic Studies and Da'wah, 2024)
This article examines the importance of the prophet’s education pattern in the hadith analyzing the prophet’s journey in educating his companions from mecca to medina, from secret to overt, to formal and non formal education, and an explanation of the hadith regarding the prophet’s education pattern at that time. This research uses a qualitative approach with the type of library research. The results of the research show that the prophet’s educational pattern is a very important analysis because it discusses the education carried out by the prophet which started from his family to the ignorant into believers, in this case Allah’s words regarding commands emerged. The prophet was to teach and perfect the morals of his people, and the hadiths are evidence of the educational pattern that the prophet had implemented.